De sitter invariant special relativity and the dark energy problem - Araujo, A. [UNESP]; López, D. F. [UNESP]; Pereira, J. G. [UNESP] (My University, 2017)
Due to the existence of an invariant length at the Planck scale, Einstein special relativity is believed to break down at the scale. A possible solution to this problem is to replace the Poincaré invariant special relativity by a de Sitter invariant special relativity. Such replacement produces concomitant changes in general relativity, the most relevant being the fact that both the background de Sitter curvature and the gravitational dynamical curvature are now included in the same curvature tensor